Multi-scale fracture patterns and their effects on gas enrichment in tight sandstones: a case study of the Upper Paleozoic in the Qingshimao gas field, Ordos Basin, China - Wang, Jie; Wang, Jiping; Zhang, Yuanyuan; Zhang, Daofeng; Sun, Lei; Luo, Jianning; Wang, Wei; Gong, Lei; Liu, Zongbao; Gao, Shuai (Frontiers in Earth Science, 2024)
A well-connected network formed by multi-scale fractures is a key factor in the formation of high-quality reservoirs and the achievement of high and stable oil and gas production in tight sandstones. Taking the Upper Paleozoic of the Qingshimao gas field in the Ordos Basin, China, as an example, based on data from image logs, cores, and thin sections, fine quantitative characterization of multi-scale natural fractures in tight sandstone reservoirs was carried out. We also established a method for dividing network patterns of multi-scale fractures and discussed the effect of each fracture network pattern on the gas enrichment and production capacity. Results indicate regular changes in the length, density, aperture, porosity, permeability, and connectivity of natural fractures at different scales. Based on the spatial combination patterns and connectivity of fractures of different scales, four types of fracture network patterns were established: multi-scale fracture network with high density and multi-orientations, multi-scale fracture network with moderate-high density and dual orientations, small-scale fracture network with moderate density and dual orientations, small-scale fracture network with low density and single orientation. The first fracture network pattern can destroy the integrity of the cap layer, causing natural gas leakage. The second fracture network pattern is a favorable area for natural gas enrichment. The third fracture network pattern requires the use of hydraulic fracturing to obtain commercial airflow. The fourth fracture network pattern has little effect on reservoir control and storage. The study of natural fractures in tight sandstone reservoirs is usually based on a single-scale perspective. Understanding the development characteristics of multi-scale fractures and their controlling effects on the reservoir helps to comprehensively understand the spatial configuration relationship of multi-scale fracture network structure patterns and promotes the development of multi-scale fractures in tight reservoir research.